2012
DOI: 10.1371/journal.pone.0033925
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Immune Activation in HIV-1 Infection Contributes to Reduced Interferon Alpha Production via Enhanced CD40:CD40 Ligand Interaction

Abstract: Although a signature of increased interferon (IFN-)alpha production is observed in HIV-1 infection, the response of circulating plasmacytoid dendritic cells (PDC) to Toll-like receptor ligand stimulation is substantially impaired. This functional PDC deficit, which we specifically observed in HIV-1 infected individuals with less than 500 CD4+ T cells/µl, is not well understood. We provide evidence that the peripheral IFN-alpha production in HIV-1 infection is actively suppressed by the enhanced interaction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 49 publications
5
29
0
Order By: Relevance
“…Although it has been observed that total sCD40L is increased in the plasma of HIV-infected subjects as compared to healthy controls [13-15], the circulating form(s) of sCD40L have not been assessed during HIV infection. The immune activating effects of multimeric sCD40L have been extensively studied [6-8], but recent studies suggest an immunosuppressive effect of monomeric sCD40L [12, 25]. To address the question of whether the monomeric or multimeric form is the predominant form of sCD40L circulating in plasma of HIV-infected subjects as compared to healthy control subjects, we enriched plasma from 8 HIV infected donors and 8 healthy control donors for medium- and low- abundance proteins, followed by immunoblot of plasma preparations for sCD40L.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although it has been observed that total sCD40L is increased in the plasma of HIV-infected subjects as compared to healthy controls [13-15], the circulating form(s) of sCD40L have not been assessed during HIV infection. The immune activating effects of multimeric sCD40L have been extensively studied [6-8], but recent studies suggest an immunosuppressive effect of monomeric sCD40L [12, 25]. To address the question of whether the monomeric or multimeric form is the predominant form of sCD40L circulating in plasma of HIV-infected subjects as compared to healthy control subjects, we enriched plasma from 8 HIV infected donors and 8 healthy control donors for medium- and low- abundance proteins, followed by immunoblot of plasma preparations for sCD40L.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that multiple forms of sCD40L, including monomers (18kD) and multimers of various sizes (26-40kD) circulate in the plasma of both HIV-infected subjects and healthy controls with relative ratios that vary by donor (Figure 1A). To better understand the implication of our finding in HIV infection, where overall levels of plasma sCD40L are heightened [13-15], we next sought to determine whether there were differential immunological effects of sCD40L forms on healthy control DCs in vitro, using sCD40L concentrations tested in previous reports[12, 25]. We observed that maturation of DCs (purity>95% CD11c+LIN neg , Figure 1B) as assessed by CD86 expression was much higher after stimulation with multimeric sCD40L as compared to monomeric sCD40L (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations